2011
DOI: 10.1016/j.gaceta.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Transmisibilidad y gravedad de la pandemia de gripe A(H1N1)2009 en España

Abstract: The estimates of R(0) for the growth phase of the pandemic wave were in the lower range of estimates of this parameter in previous pandemics. Mortality indicators calculated in the pandemic period showed an increase in deaths compared with previous interpandemic seasons, which was most pronounced in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 41 The most commonly used determinant of the transmission potential is the basic reproduction number, which is defined as the expected number of secondary cases arising from a typical primary case throughout its entire course of infection in a fully susceptible population. 42 , 43 , 44 One of the methods to estimate the reproduction number is to use the growth rate of the cumulative incidence of cases during the exponential growth phase of the pandemic. 44 As can be expected, an exponential growth model estimates parameters more precisely during a pandemic's exponential growth phase.…”
Section: Discussionmentioning
confidence: 99%
“… 41 The most commonly used determinant of the transmission potential is the basic reproduction number, which is defined as the expected number of secondary cases arising from a typical primary case throughout its entire course of infection in a fully susceptible population. 42 , 43 , 44 One of the methods to estimate the reproduction number is to use the growth rate of the cumulative incidence of cases during the exponential growth phase of the pandemic. 44 As can be expected, an exponential growth model estimates parameters more precisely during a pandemic's exponential growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that many outbreaks of A(H1N1)pdm09 influenza occurred in schools and school-aged individuals were more likely to be infected101116182023242629303136. School-aged individuals facilitated the introduction and spread of A(H1N1)pdm09 influenza in households26.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance data from many countries have shown that school-aged children and young adults most likely to be infected by A(H1N1)pdm09 influenza16232426. Many outbreaks occurred in schools, presumably because of a higher density of susceptible persons10111820293031.…”
mentioning
confidence: 99%
“…The lowest mortality rate corresponded to the group between 5 and 14 years of age (0.05 per 1000 cases), which was the group with the highest confirmed pandemic virus incidence, while the highest mortality rate corresponded to patients over 64 years of age, with four deaths per 1000 cases. 26 An observation of note on comparing the age distribution of the deaths during the pandemic season vs that of previous seasonal influenza periods is the existence of a different mortality pattern in the case of influenza A/H1N1. In effect, while most of the influenza deaths corresponded to people over 60 years of age in the seasonal influenza period (98%), in the pandemic season only 28% of the recorded deaths corresponded to this same age group.…”
Section: Risk Factors----what Patients Should Be Considered At Risk mentioning
confidence: 99%
“…In effect, while most of the influenza deaths corresponded to people over 60 years of age in the seasonal influenza period (98%), in the pandemic season only 28% of the recorded deaths corresponded to this same age group. 26 Regarding mortality by risk groups, respiratory disease (asthma, chronic obstructive pulmonary disease [COPD] and other lung diseases) is the disorder most often reported among patients admitted to Spanish ICUs with influenza A/H1N1, according to the CCAES 20 registry, with a mortality rate of 16.8% in the series published by Martin-Loeches et al 5 Among patients hospitalized due to influenza A/H1N1, between 24 and 50% of the children presented antecedents of asthma, while 36% of the adults had a history of COPD. 10 Obesity is associated to a proinflammatory state and to insulin resistance that can increase the morbidity---mortality in patients infected with influenza A/H1N1.…”
Section: Risk Factors----what Patients Should Be Considered At Risk mentioning
confidence: 99%